Pentingnya Keagamaan dan Kesehatan di Masa Pandemi Menurut Ajaran Rasulullah di Desa Labuhan Papan Rokan Hilir - Yusnita Hasibuan; Radeswandri; Rian Vebrianto; Musa Thahir; Cahyani Elvira (Tasnim Journal for Community Service, 2021)
The implementation of this online seminar/webinar service program aims to fortify/self-restrain in the face of difficulties during the pandemic with a religious or religious process. This is important because religion or religion can minimize stress and mental health that occurs at this time. This service activity was carried out with Participatory Action Research (PAR) using a qualitative descriptive approach. The population in this study was Labuhan Papan Village. The sample service involved 100 people from Labuhan Papan Village. Data was taken using a questionnaire instrument (questionnaire) to find out/impression of the implementation of the service program. From the results of the analysis, it is known that the online program seminar increases the religious/religious feeling of the people of Labuhan Papan Village in carrying out worship activities by following the health protocols set by the government. For this reason, it is hoped that the people of Labuhan Papan Village will support, carry out activities by implementing health protocols, and carry out similar activities in different places so that information and knowledge can be disseminated to the entire community of Rokan Hilir Regency.